Tão assustador que você afina: um estudo do processo de desmarginalização do MMA (Mixed Martial Arts) nas mídias brasileiras - Fernandes, Rafael de Souza Bento (2014)
Since 2011, in Brazil (corresponding to a worldwide phenomenon), the MMA, which stands for Mix Martial Arts , has been conquering more and more fans, reaching the level of third most popular sport in the country (only behind Formula One and Soccer), according to Ferreira and Orsolini (2012), in a special report for the magazine Isto é Dinheiro. It s estimated that the trademark UFC (Ultimate Fighting Championship) industry, main MMA worldwide tournament, is worth around one billion dollars, not considering the segments of clothing trade, sporting products and cable TV channels, all linked to it. Under such production conditions, intensive advertising campaigns were developed in Brazil which, as analysis point out, make possible a casual disconnection from the now reformulated MMA in relation to Vale- Tudo, seen as animalism and brutal, raising it to the status of sport, in a certain sense, denying the intrinsic violence of this physical combat. This sliding of senses (named demarginalization process ) is materialized in the corpus of the study: and ad of the chain of fast-food Burger King to advertise a new sandwich that is so scary (ironically like the fighter Anderson Silva), that você afina ( you become thin ). The purpose of this study is to comprehend the mechanisms that base de diffusion/promotion of speech (in this case, the ones to value MMA), which tangs the double relation of the linguistic fact (mainly the enunciation Tão assustador que você afina ( So scary that you cowers ) of the corpus) to the history (in function of the speech production conditions of the MMA/UFC). For that, the Pêcheux s (2009) presuppositions theory for speech analysis of French orientation, the propositions of Freud (1974) and Nolasco (2001) about the restraint of violence and aggressiveness and the analysis of the media effects, according to Chauí (2006), Eco (1987; 1984), Payer (2005) and Gregolin (2003), were used.